Performance-based seismic design of steel frames using constraint control method. Issue 12 (September 2019) - Mansouri, Seyed Fazlolah; Maheri, Mahmoud R
In this article, the optimum performance-based seismic design of steel frames is performed using the novel constraint control method. This method is based on a simple concept generally used by the engineers in structural design. In this method, the most conservative member sections are initially selected and by gradually reducing the size of the sections through controlling the problem constraints, the solution tends to an optimum design. The capacity curve of the structure is evaluated through static nonlinear analysis and used for the seismic assessment, and the structural weight is optimized by controlling relative displacement constraints at performance levels of operational, immediate occupancy, life safety and collapse prevention. The performance and efficiency of the proposed algorithm in solving for optimum performance-based seismic design are assessed through solving three benchmark problems. The results show that using constraint control method drastically reduces the number of structural analyses required to reach a solution, compared to the more commonly used metaheuristic optimization methods, while producing comparable optimum solutions. For this reason, the constraint control method is found to be particularly suitable as an optimizer for solving solution-extensive problems, such as performance-based optimum design of structures.